2009
DOI: 10.1016/j.ydbio.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Fragile X Protein controls cellular proliferation by regulating cbl levels in the ovary

Abstract: FMRP is an RNA binding protein linked to the most common form of inherited mental retardation, Fragile X syndrome (FraX). In addition to severe cognitive deficits, FraX etiology includes postpubescent macroorchidism, which is thought to result from overproliferation. Using a Drosophila FraX model, we show that FMRP controls germline proliferation during oogenesis. dFmr1 null ovaries contain egg chambers with both fewer and supranumerary germ cells. The mutant germaria contain a significantly increased number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…So far, the function of FMRP in the ovary has been studied in Drosophila models, where it may be involved in germ cell and oocyte specification (Costa et al 2005, Megosh et al 2006 as well as in the maintenance of germline stem cells, probably regulating the translation of specific mRNAs via the miRNA pathway (Yang et al 2007). A role in the control of germline proliferation was also demonstrated (Epstein et al 2009), thus suggesting an early stage-specific function of Fmr1 in germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the function of FMRP in the ovary has been studied in Drosophila models, where it may be involved in germ cell and oocyte specification (Costa et al 2005, Megosh et al 2006 as well as in the maintenance of germline stem cells, probably regulating the translation of specific mRNAs via the miRNA pathway (Yang et al 2007). A role in the control of germline proliferation was also demonstrated (Epstein et al 2009), thus suggesting an early stage-specific function of Fmr1 in germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a more recent study using Drosophila dFmr1 mutants demonstrated that dFmr1 is required for germline stem cell maintenance and repression of differentiation in the ovary, probably via the miRNA pathway (Yang et al 2007). Another Drosophila FXS model showed that FMRP controls germline proliferation during oogenesis by regulating the expression of casitas B-lineage lymphoma proto-oncogene (cbl) in the developing ovary (Epstein et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These comparisons imply that the mammalian gene family probably arose by duplication from a common ancestor similar to the dFMR1 gene. Consistently, dFMRP displays conserved RNA-binding domains; tissue and subcellular expression patterns; and functional roles in mRNA trafficking and negative translational regulation (Banerjee et al, 2007;Epstein et al, 2009;Estes et al, 2008;Reeve et al, 2005;Zhang et al, 2001;. Moreover, Drosophila that lack the dFMR1 gene (dfmr1 knockouts) closely recapitulate FXS symptoms in a wide range of molecular, cellular and behavioral phenotypes (Bolduc et al, 2008;Dockendorff et al, 2002;Gatto and Broadie, 2009a;McBride et al, 2005;Pan et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…The members of the FMRP family act in the control of RNA translation in the nervous system (Epstein et al, 2009;Jin et al, 2004a;Jin et al, 2004b) and in the ovaries (Epstein et al, 2009). More interestingly, these proteins have been reported to associate and interact with components of the RNA-induced silencing complex (RISC) including AGO1 and AGO2, two members of the Argonaute protein family, which mediate post-transcriptional control through small RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, AGO1 and AGO2 can compete for binding with miRNAs and ectopic expression of Aub in the soma competes for the siRNA pathway mediated by AGO2 (Specchia et al, 2008). Such promiscuity, the known role of the FMRP protein family in small RNA metabolism (Ascano et al, 2012a;Ascano et al, 2012b;Epstein et al, 2009;Ishizu et al, 2012) and the presence of transposons in the nervous system, a key target tissue of the FMRP protein family (Lee et al, 2011;Perrat et al, 2013), prompted us to hypothesize the involvement of the Drosophila ortholog dFmr1 protein in the piRNA pathway.…”
Section: Introductionmentioning
confidence: 99%